Minimizing Propionibacterium acnes contamination in shoulder arthroplasty: use of a wound protector. Issue 11 (21st September 2018) - Smith, Mitchell L.; Gotmaker, Robert; Hoy, Greg A.; Ek, Eugene T.; Carr, Ashley; Flynn, Jennifer N.; Evans, Matthew C.
Abstract : Background: Propionibacterium acnes may be transmitted from the subdermal tissues to the deeper tissues during shoulder arthroplasty surgery, resulting in deep infection. The aim of this prospective, clinical study was to determine whether the use of a wound protector drape can lower the incidence of P. acnes in the wound during shoulder arthroplasty surgery. Methods: For a consecutive series of 47 patients undergoing shoulder arthroplasty, a wound protector drape was used during surgery, to isolate the subdermal layer from the surgeons' hands, retractors and other instruments. Microbiological swabs were taken both from the subdermal layer and the exposed drape to determine the incidence of P. acnes at both sites. Results: The overall incidence of P. acnes in the subdermal layer was 23%. A fivefold decrease in the incidence of P. acnes in the exposed superficial layer was demonstrated by use of the wound protector drape. Conclusion: Use of a wound protector drape to isolate the superficial tissue layer from the surgeons' gloves, instruments and retractors decreases the incidence of P. acnes in the surgical field. This may result in a decreased rate of transmission to the deeper tissues, and a decreased rate of P. acnes deep infection.